A sociological study of suicide during COVID-19 in India. Issue 1 (12th December 2020) - Patel, Avanish Bhai; Kumar, Sumant
Abstract : Purpose: As we know that whole world is facing global pandemic or COVID-19 for past six months including India. It has created many psychosocial problems among the millions of people of the society. Committing suicide is one of them owing to COVID-19, and it is the matter of grave concern for the social psychologists. This study is based on secondary data. The purpose of this paper is to understand the nature of suicides in Indian society during COVID-19 and to explore the factors affecting committing suicides during COVID-19. Design/methodology/approach: The secondary data have been collected for the study of suicide because of COVID-19 through various newspapers and monthly magazines. The cases of suicide because of COVID-19 have been collected between March 2020 and July 2020. The authors have used content analysis method to analyse the cases related to suicide because of COVID-19. Findings: This study finds that the nature of committing suicide is anomic, egoistic and altruistic in the current pandemic. The study also points out that most of individuals have committed suicide in this current pandemic owing to fear of corona infection and economic crises because of nationwide lock down. Originality/value: This is an original paper which is based on content analysis. Basically, the present paper has examined the nature of suicide in India because of COVID-19 and nationwide lockdown using Durkheim's perspective of suicide.